Serotonin and Dopamine Mimic Glucose-Induced Reinforcement in C. elegans: Potential Role of NSM Neurons and the Serotonin Subtype 4 Receptor - Schwartz, Elizabeth K. C.; Sosner, Eitan N.; Desmond, Hayley E.; Lum, Stephanie J.; Sze, Ji Ying; Mobbs, Charles V. (Frontiers in Physiology, 2021)
Food produces powerful reinforcement that can lead to overconsumption and likely contributes to the obesity epidemic. The present studies examined molecular mechanisms mediating food-induced reinforcement in the model system C. elegans. After a 1-hour training session during which food (bacteria) is paired with the odorant butanone, odor preference for butanone robustly increased. Glucose mimicked this effect of bacteria. Glucose-induced odor preference was enhanced similarly by prior food withdrawal or blocking glucose metabolism in the presence of food. Food- and glucose-induced odor preference was mimicked by serotonin signaling through the ser-4 receptor. Dopamine (thought to act primarily through a D1-like receptor) facilitated, whereas the D2 agonist bromocriptine blocked, food- and glucose-induced odor preference. Furthermore, prior food withdrawal similarly influenced reward produced by serotonin, dopamine, or food, implying post-synaptic enhancement of sensitivity to serotonin and dopamine. These results suggest that glucose metabolism plays a key role in mediating both food-induced reinforcement and enhancement of that reinforcement by prior food withdrawal, and implicate serotonergic signaling through the ser-4 receptor in the re-enforcing properties of food.